2008
DOI: 10.3181/0802-rm-59
|View full text |Cite
|
Sign up to set email alerts
|

MRP (ABCC) Transporters-Mediated Efflux of Anti-HIV Drugs, Saquinavir and Zidovudine, from Human Endothelial Cells

Abstract: The constituents of highly active anti-retroviral therapy (HAART) include HIV-1 protease inhibitors (HPIs) and nucleoside reverse transcriptase inhibitors (NRTIs). Endothelial cell (EC) barriers, especially the blood-brain-barrier (BBB) suppresses the entry of HAART drugs to subendothelial HIV-1 reservoirs. The ATP binding cassette (ABC) transporter family members, multidrug resistant-1 (MDR-1) and multidrug resistance-associated proteins (MRPs) can efflux both HPIs and NRTIs from intracellular compartments. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 64 publications
1
69
0
Order By: Relevance
“…Why? Anti-HIV drugs that must enter cells to exert their action can be efficiently neutralized by some cells, using primitive and innate self-defense mechanisms such as "efflux pumps" [95], which sense toxins and eject them outside of the cell. Many experts believe that this situation could be an important reason for the viral persistence and evolution in patients on ostensibly potent combination therapies.…”
Section: Hiv-1 Entry Inhibitorsmentioning
confidence: 99%
“…Why? Anti-HIV drugs that must enter cells to exert their action can be efficiently neutralized by some cells, using primitive and innate self-defense mechanisms such as "efflux pumps" [95], which sense toxins and eject them outside of the cell. Many experts believe that this situation could be an important reason for the viral persistence and evolution in patients on ostensibly potent combination therapies.…”
Section: Hiv-1 Entry Inhibitorsmentioning
confidence: 99%
“…2005;Tiwari AK, 2011). Recent studies by us, and others, have also shown that several anti-HIV-1 drugs, especially HIV protease inhibitors (HPIs) and nucleoside analog reverse transcriptase inhibitors (NRTIs) are substrates of ABC-transporters (Choo EF, 2000;Roy U, 2009) and their expression on both lymphocytes and BBB endothelial cells (ECs) can suppress drug entry into the cellular and anatomical reservoirs of HIV-1 (Eilers M, 2008;Tarbell JM. 2010;Shen S, 2010).…”
Section: The Abc Transportersmentioning
confidence: 99%
“…probenecid), and the leukotrienes (LT) receptor antagonist (e.g. MK-571), are known inhibitors of MRPs (Eilers M, 2008). A number of preclinical and clinical trials are also being carried out to discover new and more effective efflux pump inhibitors (EPIs).…”
Section: The Slc Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most anti-HIV drugs act on intracellular targets (Owen and Khoo, 2004), and a high percentage of these drugs are substrates of some efflux transporters (Eilers et al, 2008;Janneh et al, 2005Janneh et al, , 2007Weiss et al, 2007;Hayashi et al, 2006). For the class of nucleoside reverse transcriptase inhibitors (NRTI), the current backbone of HAART, their pharmacological penetration into the target tissue/cells depends not only on the presence of transporters, but also on a cascade of intracellular activation (Painter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%